PE diaphragm oil filling material and preparation method thereof
Patent Information
- Application Number
- CN202610957552.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0005](1)填充油色度较深,抗黄变性差,不能完全满足隔膜的色泽要求及长期储存稳定性要求
基础油组合物的协同复配效应:本申请通过四种基础油的合理配比,实现了碳型分布(Ca、Cn、Cp)和化学族组成(饱和烃、芳烃、极性化合物)的精确调控,使填充油的苯胺点控制在90.0℃~95.0℃的适宜范围内,从而确保填充油与UHMWPE具有良好的材料相容性,同时具备适宜的溶解能力,在萃取过程中能精确控制隔膜的孔隙率、孔径分布、电阻性能及柔韧性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of battery materials, and more specifically, to a PE separator oily filler material and its preparation method. Background Technology
[0002] Batteries are widely used in the field of rechargeable batteries due to their low cost, simple manufacturing process, and high reliability. PE separators (ultra-high molecular weight polyethylene microporous separators) are the core components of batteries, used to isolate the positive and negative electrodes, prevent short circuits, and store electrolyte. They are gradually replacing traditional rubber, PVC, and PP separators, becoming the mainstream choice.
[0003] PE separators typically employ an oil-phase filling-extrusion calendering-extraction pore-forming process, with oily filler material (filler oil) serving as the key raw material, containing approximately 55% to 65% oil in the separator. The core functions of the filler oil include: improving the flowability of the mixture of UHMWPE and fillers, aiding in extrusion molding, constructing a uniform microporous structure, and ensuring the strength and anti-aging properties of the separator.
[0004] However, existing conventional diaphragm filling oils and the diaphragms produced from them generally have the following problems:
[0005] (1) The filler oil is dark in color and has poor resistance to yellowing, which cannot fully meet the color requirements of the diaphragm and the requirements for long-term storage stability.
[0006] (2) The antioxidant properties are average. The viscosity increases rapidly under high temperature conditions, which seriously affects the high temperature thermo-oxidative aging performance of the diaphragm and the thermal degradation during the extrusion process, leading to diaphragm aging and brittleness.
[0007] (3) The filler oil contains more low-boiling-point components and has a large amount of high-temperature volatilization, which not only results in a poor operating environment, but also makes it difficult for bubbles in the diaphragm to be completely discharged during the processing, affecting product quality.
[0008] (4) The sulfur content of the filler oil is too high, which poses a risk of component corrosion under long-term high-temperature operation conditions.
[0009] (5) The high sulfur content makes it impossible to meet the acid stability test requirements. At the same time, during battery use, sulfur ions are released to the electrolyte surface during discharge to form flocculent matter, which affects battery performance.
[0010] (6) Poor material compatibility makes it difficult to completely remove excess filler oil during the extraction process, resulting in the membrane's porosity, thickness uniformity, pore size distribution, and electrical properties failing to meet higher application requirements.
[0011] Chinese patent CN118970370B discloses a battery separator filling conditioner and its preparation method, but there is still room for improvement in terms of chemical composition regulation, sulfur content control and antioxidant synergistic effect.
[0012] Therefore, there is an urgent need to develop a PE separator oil-based filler material with light color, excellent antioxidant properties, low volatility, ultra-low sulfur, good material compatibility, and superior overall performance to meet the application requirements of high-end battery separators. Summary of the Invention
[0013] To address the aforementioned technical problems in related technologies, this invention provides an oily filler material for PE diaphragms and its preparation method, which can solve the above problems.
[0014] To achieve the above-mentioned technical objectives, the technical solution of the present invention is implemented as follows: An oily filler material for PE diaphragms includes a base oil composition, a primary antioxidant, and an auxiliary antioxidant; The base oil composition includes alkylbenzene synthetic base oil, paraffinic neutral oil, naphthenic neutral oil, and Fischer-Tropsch synthetic oil; The components of the PE diaphragm oily filler material are, by weight, 98-100 parts of base oil composition, 1-2 parts of main antioxidant, and 1-2 parts of auxiliary antioxidant. The components in the base oil composition are, by weight, 30-40 parts of alkylbenzene synthetic base oil, 20-30 parts of paraffinic neutral oil, 10-15 parts of naphthenic neutral oil, and 15-25 parts of Fischer-Tropsch synthetic oil, and the sum of the weight parts of the four oil components is 98-100 parts.
[0015] Furthermore, the alkylbenzene synthetic base oil is alkylbenzene synthetic base oil (AB-1); the paraffinic neutral oil is paraffinic neutral oil (SN-2); the naphthenic neutral oil is naphthenic neutral oil (DN-3); and the Fischer-Tropsch synthetic oil is Fischer-Tropsch synthetic oil C32-36 (CT-4).
[0016] Furthermore, the primary antioxidant is 2,6-di-tert-butylphenol; the secondary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite.
[0017] Furthermore, the PE diaphragm oily filler material contains sulfur with a mass fraction ≤0.01%, polar compounds with a mass fraction ≤0.50%, and saturated hydrocarbons with a mass fraction ≥98.00%.
[0018] A method for preparing an oily filler material for a PE diaphragm includes the following steps: S1: Preparation of base oil composition A: Alkylbenzene synthetic base oil, paraffinic neutral oil, naphthenic neutral oil and Fischer-Tropsch synthetic oil are placed in a container, heated and stirred, and the temperature is raised to the specified range to obtain base oil composition A; S2: Adding excipients: Add the main antioxidant and auxiliary antioxidant to the blending tank in sequence, mix with base oil composition A, stir at a constant temperature, and prepare mixture B; S3: Vacuum dehydration treatment: Mixture B is subjected to vacuum dehydration treatment to obtain mixture C; S4: Cooling and filtration: Cool and filter the mixture C to obtain the PE membrane oily filler material.
[0019] Furthermore, in S1, the container is a vacuum drying kettle, the stirring time is 30 minutes, and the temperature is raised to 60℃~70℃.
[0020] Furthermore, in S2, the constant temperature is 65°C and the stirring time is 60 min.
[0021] Furthermore, in step S3, the vacuum degree of vacuum dehydration is ≥-0.095MPa, and the process is repeated 2 to 3 times.
[0022] Furthermore, in step S4, the temperature is cooled to 30°C to 40°C, and the filtration accuracy is 1µm.
[0023] The beneficial effects of this invention are: Synergistic effect of base oil composition: This application achieves precise control of carbon type distribution (Ca, Cn, Cp) and chemical group composition (saturated hydrocarbons, aromatics, polar compounds) through the reasonable ratio of four base oils, so that the aniline point of the filler oil is controlled within a suitable range of 90.0℃ to 95.0℃, thereby ensuring that the filler oil has good material compatibility with UHMWPE, while having suitable solubility, and can precisely control the porosity, pore size distribution, electrical properties and flexibility of the diaphragm during the extraction process.
[0024] Ultra-low sulfur content and polar compound control: This invention selects low-sulfur base oil raw materials and combines them with precise compounding ratios to ensure that the sulfur content of the filler oil is ≤0.01% (mass fraction), the polar compound content is ≤0.50% (mass fraction), and the saturated hydrocarbon content is ≥98.00% (mass fraction). This technology effectively solves the problems caused by sulfur ions ionizing to the electrolyte surface during discharge and the formation of flocculent matter due to high polar compound content, which in turn leads to short circuits, plate sulfation, plate heating, and a surge in self-discharge, significantly improving battery safety and lifespan.
[0025] Excellent antioxidant properties: This invention employs a synergistic compound system of primary and secondary antioxidants. The primary antioxidant, acting as a free radical scavenger, effectively terminates chain oxidation reactions; the secondary antioxidant, acting as a peroxide decomposer, decomposes peroxides generated during oxidation. The synergistic effect of both significantly improves the oxidation stability of the filler oil (≥800 min measured by rotating oxygen bomb method), effectively inhibits rapid viscosity growth under high-temperature conditions, enhances the diaphragm's resistance to heat and oxygen aging, prevents diaphragm aging and embrittlement, and extends the diaphragm's service life.
[0026] Excellent comprehensive physicochemical properties: light color (≤2.5), ensuring excellent membrane color and storage stability; moderate kinematic viscosity (120.0~150.0 cst at 40℃), excellent porosity; high flash point (≥230℃), low evaporation loss (≤1.5%), safe extrusion molding operation, and good environmental performance; low pour point (≤-20℃), good low-temperature fluidity; extremely low acid value (≤0.02 mgKOH / g), non-corrosive to equipment; passed acid stability test (38% sulfuric acid, uncarbonized), demonstrating excellent acid resistance.
[0027] Excellent recyclability: Due to the excellent antioxidant and thermal stability of the filler oil of this invention, the viscosity of the filler oil after extraction and recovery changes little, and it can be recycled multiple times with high utilization rate, effectively reducing production costs and having good economic and environmental benefits. Detailed Implementation
[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention. Example 1:
[0029] (I) Preparation of base oil composition A 32 parts of alkylbenzene synthetic base oil (AB-1), 28 parts of paraffinic neutral oil (SN-2), 15 parts of naphthenic neutral oil (DN-3), and 23 parts of Fischer-Tropsch synthetic oil C32-36 (CT-4) were placed in a vacuum drying kettle, stirred and heated to 60℃-70℃ for 30 minutes to obtain base oil composition A.
[0030] (II) Preparation of Mixture B One part of the main antioxidant (2,6-di-tert-butyl mixed phenol) and one part of the auxiliary antioxidant (tris(2,4-di-tert-butylphenyl) phosphite) were added to the mixing tank in sequence and mixed with the base oil composition A. The mixture was kept at a constant temperature of 60°C and stirred for 60 minutes to prepare mixture B.
[0031] (III) Preparation of novel PE diaphragm oily filler material Mixture B was subjected to a vacuum dehydration process. The vacuum pump was set to a vacuum degree of ≥-0.095 MPa, the number of cycles was 2 to 3, the cooling device temperature was set to 30 to 40℃, and the filtration accuracy was 1 μm, to obtain a novel PE membrane oily filler material.
[0032] The test results for various indicators of the product in Example 1 are shown in the table below: Example 2:
[0033] (I) Preparation of base oil composition A 36 parts of alkylbenzene synthetic base oil (AB-1), 26 parts of paraffinic neutral oil (SN-2), 14 parts of naphthenic neutral oil (DN-3), and 22 parts of Fischer-Tropsch synthetic oil C32-36 (CT-4) were placed in a vacuum drying kettle, stirred and heated to 60℃-70℃ for 30 minutes to obtain base oil composition A.
[0034] (II) Preparation of Mixture B One part of the main antioxidant (2,6-di-tert-butyl mixed phenol) and two parts of the auxiliary antioxidant (tris(2,4-di-tert-butylphenyl) phosphite) were added to the mixing tank in sequence and mixed with the base oil composition A. The mixture was kept at a constant temperature of 60°C and stirred for 60 minutes to prepare mixture B.
[0035] (III) Preparation of novel PE diaphragm oily filler material Mixture B was subjected to a vacuum dehydration process. The vacuum pump was set to a vacuum degree of ≥-0.095 MPa, the number of cycles was 2 to 3, the cooling device temperature was set to 30 to 40℃, and the filtration accuracy was 1 μm, to obtain a novel PE membrane oily filler material.
[0036] The test results for various indicators of the product in Example 2 are shown in the table below: Example 3:
[0037] (I) Preparation of base oil composition A 39 parts of alkylbenzene synthetic base oil (AB-1), 29 parts of paraffinic neutral oil (SN-2), 13 parts of naphthenic neutral oil (DN-3), and 18 parts of Fischer-Tropsch synthetic oil C32-36 (CT-4) were placed in a vacuum drying kettle, stirred and heated to 60℃-70℃ for 30 minutes to obtain base oil composition A.
[0038] (II) Preparation of Mixture B Two parts of the main antioxidant (2,6-di-tert-butyl mixed phenol) and one part of the auxiliary antioxidant (tris(2,4-di-tert-butylphenyl) phosphite) were added to a mixing tank in sequence and mixed with base oil composition A. The mixture was kept at a constant temperature of 60°C and stirred for 60 minutes to prepare mixture B.
[0039] (III) Preparation of novel PE diaphragm oily filler material Mixture B was subjected to a vacuum dehydration process. The vacuum pump was set to a vacuum degree of ≥-0.095 MPa, the number of cycles was 2 to 3, the cooling device temperature was set to 30 to 40℃, and the filtration accuracy was 1 μm, to obtain a novel PE membrane oily filler material.
[0040] The test results for various indicators of the product in Example 3 are shown in the table below:
[0041] In summary, compared with existing technologies, the novel PE separator oil-based filler material prepared by the process provided in this disclosure, and the battery separator material manufactured using it, have the following characteristics and performance advantages: the filler oil has a light color, ensuring the color and storage stability requirements of the separator; the viscosity is moderate, and the porosity is excellent; the flash point is high, the evaporation loss is low, and the extrusion molding operation is safe; compared with the original technology of patent CN118970370B (a battery separator filler conditioner and its preparation method), this invention selects the unique physical properties of alkylbenzene synthetic base oil (AB-1) and Fischer-Tropsch synthetic oil C32-36 (CT-4) (such as carbon type distribution, chemical group composition, sulfur content, flash point, among which alkylbenzene synthetic base oil (AB-1) has a high Ca value, the other three base oils have extremely low Ca values, and the saturated hydrocarbon content, polar matter content, and sulfur content of the four base oils are all superior to those of similar base oils, and Fischer-Tropsch synthetic oil C32-36 (CT-4) has an ultra-high flash point), and compared with existing technologies, the PE separator oil has the following advantages: the filler oil has a light color, ensuring the color and storage stability requirements of the separator; the filler oil has a moderate viscosity and excellent porosity; the filler oil has a high flash point; the filler oil has a high viscosity and excellent porosity ... A reasonable ratio of wax-based neutral oil (SN-2) and naphthenic neutral oil (DN-3) is used to control the polar content in the chemical composition of the filler oil and to control the sulfur content to an extremely low level. This fully leverages the advantages and synergistic effects of each component, greatly solving problems such as short circuits, plate sulfation, plate heating, and increased self-discharge caused by sulfur ions ionizing to the electrolyte surface during discharge and high polar content leading to flocculent formation during battery use. Appropriate aniline point and carbon form distribution design ensures good material compatibility of the filler oil. High saturated hydrocarbon content gives the filler oil good thermal stability. The synergistic effect of the primary and secondary antioxidants significantly enhances the filler oil's own antioxidant capacity and, to some extent, improves the aging resistance of the separator. Suitable solubility allows for effective control of the separator's porosity, pore size, resistivity, flexibility, and sealability during extraction. The extracted and recovered filler oil exhibits minimal viscosity change, high reuse rate, and controllable cost.
[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An oily filler material for PE diaphragms, characterized in that, Includes base oil composition, primary antioxidant, and secondary antioxidant; The base oil composition includes alkylbenzene synthetic base oil, paraffinic neutral oil, naphthenic neutral oil, and Fischer-Tropsch synthetic oil; The components of the PE diaphragm oily filler material are, by weight, 98-100 parts of base oil composition, 1-2 parts of main antioxidant, and 1-2 parts of auxiliary antioxidant. The components in the base oil composition are, by weight, 30-40 parts of alkylbenzene synthetic base oil, 20-30 parts of paraffinic neutral oil, 10-15 parts of naphthenic neutral oil, and 15-25 parts of Fischer-Tropsch synthetic oil, and the sum of the weight parts of the four oil components is 98-100 parts.
2. The PE diaphragm oily filler material according to claim 1, characterized in that, The alkylbenzene synthetic base oil is alkylbenzene synthetic base oil (AB-1); the paraffinic neutral oil is paraffinic neutral oil (SN-2); the naphthenic neutral oil is naphthenic neutral oil (DN-3); and the Fischer-Tropsch synthetic oil is Fischer-Tropsch synthetic oil C32-36 (CT-4).
3. The PE diaphragm oily filler material according to claim 1, characterized in that, The primary antioxidant is 2,6-di-tert-butylphenol; the secondary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite.
4. The PE diaphragm oily filler material according to claim 1, characterized in that, The PE diaphragm oil-based filler material contains sulfur with a mass fraction of ≤0.01%, polar compounds with a mass fraction of ≤0.50%, and saturated hydrocarbons with a mass fraction of ≥98.00%.
5. A method for preparing the PE diaphragm oily filler material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: Preparation of base oil composition A: Alkylbenzene synthetic base oil, paraffinic neutral oil, naphthenic neutral oil and Fischer-Tropsch synthetic oil are placed in a container, heated and stirred, and the temperature is raised to the specified range to obtain base oil composition A; S2: Adding excipients: Add the main antioxidant and auxiliary antioxidant to the blending tank in sequence, mix with base oil composition A, stir at a constant temperature, and prepare mixture B; S3: Vacuum dehydration treatment: Mixture B is subjected to vacuum dehydration treatment to obtain mixture C; S4: Cooling and filtration: Cool and filter the mixture C to obtain the PE membrane oily filler material.
6. The preparation method according to claim 5, characterized in that, In step S1, the container is a vacuum drying kettle, the stirring time is 30 minutes, and the temperature is raised to 60℃~70℃.
7. The preparation method according to claim 5, characterized in that, In step S2, the constant temperature is 65°C and the stirring time is 60 minutes.
8. The preparation method according to claim 5, characterized in that, In step S3, the vacuum degree of vacuum dehydration is ≥-0.095MPa, and the process is repeated 2 to 3 times.
9. The preparation method according to claim 5, characterized in that, In step S4, the temperature is cooled to 30°C to 40°C, and the filtration accuracy is 1µm.
Citation Information
Patent Citations
A battery separator filling conditioner and preparation method thereof
CN118970370B